Increasing the Explosive Power Through Plyometric Training in Athletes Under 18 Years Old - Cristian SANTA; Andrei CRISAN; Onela SANTA (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae)
Increasing the explosive power through plyometric training is one of the most important aspects of sports, especially in team sports, regardless of players’ training level. Explosive power represents muscles’ ability to generate force quickly and is crucial for achieving a high vertical jump. Plyometric training, also known as jump training or explosive power training, is an essential method in preparing athletes to improve their physical performance, particularly in sports that require explosive strength and speed. Methods: The testing was conducted on two junior groups from the "School Sports Club" and BC 2B Sports Zalău, from the sports disciplines of volleyball and basketball, over a period of two and a half months. Objective: The objective of this study are to prove that the explosive power can be increased through plyometric training in athletes under 18 years old. Results: The analysis of the results was conducted after doing both the initial tests and the final tests for test 1, Sargent Jump Test from standing position, and test 2, Sargent Jump Test with full approach. Both teams completed the same tests, and the results were as follows: Volleyball team’s first test showed increasing numbers - from 1 centimeters to 11 centimeters; Basketball team’s first test showed increasing numbers- from 1 centimeters to 16 centimeters; Voleyball team’s second test showed improved numbers - from 3 centimeters to 15 centimeters; Basketball team’s second test showed improved numbers - from 0 centimeters to 19 centimeters. Conclusion: In summary, based on the results, this research has shown that plyometric training is an essential and efficient method for increasing the explosive power, developing the vertical jump and boosting the physical performance of young athletes. Some subjects achieved good results in both tests, while others excelled in only one; however, the average results indicated that the hypothesis was confirmed.